Automatic Ceiling Fan Control Using Temperature and Room Occupancy - Kommey, Benjamin; Dunyo, John Kwame; Akowuah, Bright Yeboah; Tamakloe, Elvis (Universitas Andalas, 2022)
This paper presents the design and implementation of an automatic ceiling fan speed regulator using web camera and a temperature sensor. Fans have become a very important aspect of our daily lives to present us with comfort especially in hot climates. However, they come with some attendant issues such as a person having to move to where the fan regulators are placed to be able to adjust the speed of the fan. This can be difficult as temperatures change during the day as well as at night when one is asleep. This also poses a problem for physically challenged individuals with mobility difficulties. This project seeks to design a solution that involves automatic fan regulation. This was achieved using a temperature sensor, a camera that captures images, and a system intelligent unit that processes the captured images to detect occupancy. The speed of the fan is then automatically adjusted based on the room temperature and occupancy. The system was implemented on a raspberry pi, a resource constrained edge computing environment.